Effects of mood on critical thinking. (March 2023) - Lun, Vivian Miu-Chi; Yeung, June Chun; Ku, Kelly Yee Lai
Highlights: Positive mood and negative mood are both beneficial to critical thinking (CT). Daily variation in positive mood enhances performance in Halpern CT Assessment. Variation in positive mood enhances CT in Halpern test forced-choice questions. Anxiety relates better with CT than positive mood using mood induction procedures. Abstract: Critical thinking is an important goal in education. The relation between mood and critical thinking is yet to be systematically investigated. In two studies, we examined how mood relates to students' critical thinking performance in standard assessment. Study 1 involved daily sampling of 191 college students' mood for a week prior to assessment of critical thinking with the Halpern Critical Thinking Assessment (HCTA) which comprises open-ended and forced-choice questions. These students were also assessed for their need for cognition and general intelligence in the first test session. Results showed that daily variation in positive mood significantly predicted the overall score in critical thinking assessment, and the effect was more salient in forced-choice questions. These effects were unrelated to the students' need for cognition and general intelligence. Study 2 adopted mood induction procedures to elicit positive or negative mood among 115 college students. Participants who were induced to experience negative mood performed better in critical thinking assessment than their counterparts who experienced positive mood induction. Altogether, the findings showed that mood could influence critical thinking. The findings are discussed in terms of practical implications and future research direction.